Fostering Entrepreneurial Learning On‐the‐Job: evidence from innovative small and medium‐sized companies in Europe. (June 2016) - Baggen, Yvette; Lans, Thomas; Biemans, Harm J. A.; Kampen, Jarl; Mulder, Martin
Abstract: As economies become more innovation‐driven, the need for entrepreneurial behaviour amongst employees working for existing companies increases in order to enhance the organisations' capacity to develop new ideas, products and services. Hence, entrepreneurial learning and the development of entrepreneurial competencies of employees on‐the‐job become more important. One of the most crucial competencies in this regard is the ability to identify potential business opportunities, referred to as opportunity identification competence (OIC). In this empirical study, antecedents of OIC were investigated in a small and medium‐sized business context. Based on the 3‐P (i.e. presage, process, product) model, specific learner, work environment, and process factors influencing OIC as an outcome variable were studied. More than 200 employees from 12 companies completed a questionnaire. Results of a backward regression analysis underline the importance of investing in programmes that focus on entrepreneurial learning at the shop floor level, trusting employees that they are capable of actively participating in the early stages of innovation and the crucial role of owner‐managers to support entrepreneurial employee activities.